Economics of Minimalist Transcatheter Aortic Valve Replacement: Results From the 3M-TAVR Economic Study. (18th October 2022) - Butala, Neel M.; Wood, David A.; Li, Haiyan; Chinnakondepalli, Khaja; Lauck, Sandra B.; Sathananthan, Janarthanan; Cairns, John A.; Magnuson, Elizabeth A.; Barker, Madeleine; Webb, John G.; Welsh, Robert; Cheung, Anson; et al.
Abstract : Background: The 3M-TAVR trial (3M-Transcatheter Aortic Valve Replacement) demonstrated the feasibility and safety of next-day hospital discharge after transfemoral TAVR with implementation of a minimalist pathway. However, the economic impact of this approach is unknown. Therefore, we evaluated costs for patients undergoing minimalist TAVR compared with conventional TAVR. Methods: We used propensity matching to compare resource utilization and costs (from a US health care system perspective) for patients in the 3M-TAVR trial with those for transfemoral TAVR patients enrolled in the contemporaneous S3i trial (PARTNER SAPIEN-3 Intermediate Risk). Procedural costs were estimated using measured resource utilization for both groups. For the S3i group, all other costs through 30-day follow-up were assessed by linkage with Medicare claims; for 3M, these costs were assessed using regression models derived from S3i cost and resource utilization data. Results: After 1:1 propensity matching, 351 pairs were included in our study (mean age 82, mean Society of Thoracic Surgery risk score 5.3%). There were no differences in death, stroke, or rehospitalization between the 3M-TAVR and S3i groups through 30-day follow-up. Index hospitalization costs were $10 843/patient lower in the 3M-TAVR cohort, driven by reductions in procedure duration, anesthesia costs, and length of stay. Between discharge and 30 days, costs were similar for the 2 groups such that cumulative 30-day costs were $11 305/patient lower in the 3M-TAVR cohort compared with the S3i cohort ($49 425 versus $60 729, 95% CI for difference $9378 to $13 138; P <0.001). Conclusions: Compared with conventional transfemoral TAVR, use of a minimalist pathway in intermediate-risk patients was associated with similar clinical outcomes and substantial in-hospital cost savings, which were sustained through 30 days. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02287662.